Determinación de una correlación de comportamiento de afluencia para flujo multifásico que se ajuste a las condiciones de las arenas B- formación mugrosa de campo Llanito (2017)
This degree thesis presents the development of an Inflow Performance Relationship (IPR) for the Llanito Field - Zone B of Ecopetrol S.A. It is evidenced that the Inflow Performance Relationship (IPR) proposed by Vogel in 1968 can not be generalized for wells producing under multiphase flow conditions, because it overestimates the production potentials of the wells. In order to obtain a generalized IPR correlation of the Llanito Field - Zone B, it was necessary to perform numerical simulation runs of the reservoirs using the Eclipse 100 black oil simulator. The runs were made for eight wells representative of the field of study, observing a differentiated behavior in the Results of the trend of the Vogel method for reservoir pressures lower than 1300 psi.